Self-organized nanostructured anodic oxides for display applications - Jaguiro, P.; Stsiapanau, A.; Hubarevich, A.; Mukha, Y.; Smirnov, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Electrochemical technologies have a high potential for display applications because of their cheapness and simplicity, easiness to scaling to large substrates and lowtemperature nature. However, in major display technologies the oxide films should be deposited on transparent conductive substrate, usually ITO on glass. For dielectric substrates like glasses, a special technology of current control is applied to anodizing metal films, which changes the oxide porous structure in a final stage and prevents formation of metal islands. To transform the residual metal nanowires into oxide, a special fading process similar to anoding bonding can be done. Usually, high reactivity electrolytes are used in the anodizing process, which destroys ITO layers. We have analyzed chemical properties of ITO in various anodizing electrolytes and found some suitable reagents and compositions. A lot of functional layers can be created by anodizing. For example, different filters may be formed by filling the pores by ink jet printing. Porous oxides can have low refractive indexes – lower than any bulk material, and can be used as effective antireflective coatings. A titanium oxide cover film forms “self-cleaning” surface due to its semiconductor photonics properties and oxygen production.